Pertentangan Asas Perundang-undangan dalam Pengaturan Larangan Mobilisasi Anak pada Kampanye Pemilu - Suriyani, Meta (Jurnal Konstitusi, 2016)
Article 32 paragraph (1) letter k Election Commission Regulation No. 15 Year 2013 describes implementers, participants, and officials are prohibited from mobilizing campaigns Indonesian citizens who do not meet syarats as Voters. However, Law No. 8 of 2012 on General Election of DPR, DPD and DPRD itself, does not expressly prohibit the mobilization of Indonesian citizens who do not yet qualify as a selector or exploitation of children in political activities, including campaign. So that the Commission regulation violates the hierarchy of legislation that is in of commencement shall contrary to the Law on Election of Members of Legislative as higher regulations. Therefore, it is also not in line with Law No. 35 of 2014 on the Amendment of Act No. 23 of 2002 on Child Protection. Mobilization of children in the activities of the election campaign is the deprivation of the rights of the child. Intentionally or unintentionally, the actual implementers, participants, and campaign officers have done wrong treatment (exploitation) by mobilizing children who do not qualify as voters in political activities in the activities of the election campaign for the DPR, DPD and DPRD held at central and regional levels occur in almost all parts of Indonesia.